The basics of IT audit : purposes, processes, and practical information - Gantz, Stephen D. (The basics, 2014)
"Dependence on information technology (IT) is a characteristic common to virtually all modern organizations. Organizations rely on information, and the processes and enabling technology needed to use and effectively manage information. This reliance characterizes public and private sector organizations, regardless of mission, industry, geographic location, or organization type. IT is critical to organizational success, operating efficiency, competitiveness, and even survival, making imperative the need for organizations to ensure the correct and effective use of information technology. In this context it is important that resources are efficiently allocated, that IT functions at a sufficient level of performance and quality to effectively support the business, and that information assets are adequately secured consistent with the risk tolerance of the organization. Such assets must also be governed effectively, meaning that they operate as intended, work correctly, and function in a way that complies with applicable regulations and standards. IT auditing can help organizations achieve all of these objectives"--